A Murder in Paris (A Year in Europe-Book 1) - Blake, Pierce (Lukeman Literary, 2021)
"When you think that life cannot get better, Blake Pierce comes up with another masterpiece of thriller and mystery! This book is full of twists, and the end brings a surprising revelation. Strongly recommended for the permanent library of any reader who enjoys a very well-written thriller."--Books and Movie Reviews (re Almost Gone) A MURDER IN PARIS is the debut novel in a charming new cozy mystery series by USA Today bestselling author Blake Pierce, whose #1 bestseller Once Gone has received 1,500 five-star reviews.Diana Hope, 55, is still adjusting to her recent separation when she discovers her ex-husband has just proposed to a woman 30 years younger. Secretly hoping they would reunite, Diana is devastated. She realizes the time has come to reimagine life without him-in fact, to reimagine her life, period.Devoting the last 30 years of her life to being a dutiful wife and mother and to climbing the corporate ladder, Diana has been relentlessly driven, and has not taken a moment to do anything for herself. Now, the time has come.Diana never forgot her first boyfriend, who begged her to join him for a year in Europe after college. She had wanted to go so badly, but it had seemed like a wild, romantic idea, and a gap year, she'd thought, would hinder her resume and career. But now, with her daughters grown, her husband gone, and her career no longer fulfilling, Diana realizes it's time for herself-and to take that romantic year in Europe she'd always dreamed of.Diana prepares to embark on the year of her life, finally turning to her bucket list, hoping to tour the most beautiful sights and sample the most scrumptious cuisines-and maybe, even, to fall in love again. But a year in Europe may have different plans in store for her. Can A-type Diana learn to go with the flow, to be spontaneous, to let down her guard and to learn to truly enjoy life again?In A MURDER IN PARIS (Book #1), Diana hopes to kick off her journey, and find new love, with an unforgettable night at the Versailles ball. But when the dramatic night takes a harrowing turn she could never expect, Diana realizes she will have to solve the crime-or else have her trip end in disaster.A YEAR IN EUROPE is a charming and laugh-out-loud cozy mystery series, packed with food and travel, with mysteries that will leave you on the edge of your seat, and with experiences that will leave you with a sense of wonder. As Diana embarks on her quixotic quest for love and meaning, you will find yourself falling in love and rooting for her. You will be in shock at the twists and turns her journey takes as she somehow finds herself at the center of a mystery, and must play amateur sleuth to solve it. Fans of books like Eat, Pray, Love and Under the Tuscan Sun have finally found the cozy mystery series they've been hoping for!Book #2 (DEATH IN FLORENCE) and book #3 (VENGEANCE IN VIENNA) in the series are now also available!
Keywords: Krimi, detektivky